Analysis of the Causes of Students Lack of Creativity in SBdP Learning Pencil Drawstring Collage Works - Pramesti, Ardhya; Ary, Deasylina da (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2024)
This research was conducted to determine the causes of the lack of creativity in fourth grade students at Kanisius Beringin Elementary School. This type of research is qualitative-descriptive research with the method used is the case study method, where the data collection techniques collected were obtained through observation, interviews and documentation of the research subjects. The results of this research prove that there are several factors causing students' lack of creativity in learning pencil draw collage work, including: 1) Teacher factors, 2) Student factors, 3) Facilities and infrastructure factors, 4) Family and environmental factors. The lack of creativity of fourth grade students at Kanisius Beringin Elementary School in pencil drawing collage material makes it difficult for students to develop their ideas, apart from that, the lack of motivation, inspiration and also students' freedom in imagination makes this one of the causes of students' lack of creativity, resulting in close collaboration between teachers, students, parents and schools are needed to create a learning environment that supports, stimulates and facilitates the optimal development of student creativity. The solution that can be provided by researchers is that teachers can take simple actions, such as paying more attention to the learning methods used. Learning methods are one of the important things in the continuity of learning in order to achieve good learning goals and can provide more motivation to students and provide freedom and opportunity. for them to explore more deeply, in learning Pencil Shaved Collage Work.